MENDARAS MANUNGGALING KAWULA GUSTI SYEKH SITI JENAR - Ahmad Sidqi (LP2M IAIN Tulungagung, 2017)
that make Jenar’s controversial is a God-theme things, that make hakikatis most important things than syari’at. Manunggaling kawula Gusti as ahogher thing of Jenar also gift a controversial status to Jenar. It can happened,because the approachment of Jenar too less of manunggaling kawula Gusti,that is language approachment. Need an approacment objectively of Jenar,Human being is a human that showing if empthy actually Full (Jenar’swith his thought, actually not been himself as God, but on his thought, Jenarwant to say that God is One.Keyword: Syekh Siti Jenar, Tasawuf, Manunggaling Kawula Gusti,